Meeting the demands of a multi-dimensional professional writing course for tertiary students - Ang, Pei Soo; Menon, Rema (2018)
What distinguishes English for Specific Purpose (ESP) from General English (GE) is not the existence of a need but the awareness of it (Hutchinson & Waters, 1987). And thus, in designing a compulsory English course for advanced users of English (CEFR B2/Low C1), the Faculty of Languages & Linguistics, University of Malaya (a Malaysian public university) faces the challenge of meeting the multi-dimensional demands of a holistic ESP course. Hence, this paper concerns how we have aligned the course design of an advanced professional writing course for tertiary students with the various institutional demands to equip undergraduates with employable skills particularly writing skills for the workplace. We also evaluate the course feedback received over 3 semesters to gauge the achievement of the intended learning outcomes.